2018
DOI: 10.1097/dad.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine-Centric Melanocytic Nevus

Abstract: Benign melanocytic neoplasms present with a diverse array of well-known histopathologic patterns. It is imperative to recognize the benign patterns to render accurate diagnoses. We describe here an interesting and hitherto not described low-power architectural pattern of a benign melanocytic lesion: eccrine-centric melanocytic nevus. The patient was a 50-year-old African American woman who noticed a new mole on her foot that began as a dark speck but quickly grew larger. The lesion was excised to exclude the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Sardana et al 4 suggested that the term “congenital follicular melanocytic nevi” is more appropriate for this presentation rather than “spotted grouped pigmented nevus type I.” Mishima used the term “eccrine‐centered nevus” and reported a trio of nevi demonstrating proliferations of melanocytes that centered on the eccrine structures in both dermal and epidermal locations. However, this term refers to histopathologic features that are described in other clinical conditions as well 4,5,10 …”
Section: Discussionmentioning
confidence: 99%
“…Sardana et al 4 suggested that the term “congenital follicular melanocytic nevi” is more appropriate for this presentation rather than “spotted grouped pigmented nevus type I.” Mishima used the term “eccrine‐centered nevus” and reported a trio of nevi demonstrating proliferations of melanocytes that centered on the eccrine structures in both dermal and epidermal locations. However, this term refers to histopathologic features that are described in other clinical conditions as well 4,5,10 …”
Section: Discussionmentioning
confidence: 99%